2017
DOI: 10.1177/0146167217713192
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Origins of Freedom: Pathogens, Heat Stress, and Frontier Topography Predict More Vertical but Less Horizontal Governmental Restriction

Abstract: What kinds of physical environments make for free societies? The present research investigates the effect of three different types of ecological stressors (climate stress, pathogen stress, and frontier topography) on two measurements of governmental restriction: Vertical restriction involves select persons imposing asymmetrical laws on others, while horizontal restriction involves laws that restrict most members of a society equally. Investigation 1 validates our measurements of vertical and horizontal restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 72 publications
4
58
0
Order By: Relevance
“…Conway et al. () produced markers of legal discrimination for each U.S. state that were parallel to those used across nations. We used the median latitude and median longitude in each state to predict this marker of legal discrimination within the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conway et al. () produced markers of legal discrimination for each U.S. state that were parallel to those used across nations. We used the median latitude and median longitude in each state to predict this marker of legal discrimination within the United States.…”
Section: Discussionmentioning
confidence: 99%
“…To showcase how this can be done, we used available data to explore a within-country test of the north-south perspective on one of the markers of conflict attitudes used in our cross-national analyses: legal discrimination. Conway et al (2017) produced markers of legal discrimination for each U.S. state that were parallel to those used across nations. We used the median latitude and median longitude in each state to predict this marker of legal discrimination within the United States.…”
Section: Implications: Northerners Versus Southernersmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the last weakness, consider the following study on two kinds of freedom. Conway et al (2017) made a distinction between vertical restrictions of freedoms by select persons imposing asymmetrical laws on others, and horizontal restrictions through laws that constrain most members of a society equally. They then showed that much ecological stress (heat stress, parasite stress, and frontier topography stress) tends to increase vertical restrictions and decrease horizontal restrictions of freedoms.…”
Section: Discussionmentioning
confidence: 99%
“…Cold stress, by contrast, leads to less vertical restrictions of freedoms, especially in rich countries, and to more horizontal restrictions of freedoms irrespective of the country’s level of wealth. So, Conway et al’s (2017) study about the ecological origins of freedoms exposes the incompleteness of the present exploration by directing full attention to the co-occurring cultural dynamics of freedoms for some and freedoms for all. We strongly encourage more time- and location-sensitive analyses of such processes at different time and geographic scales.…”
Section: Discussionmentioning
confidence: 99%